1983
DOI: 10.1001/archsurg.1983.01390020017003
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of In Vitro Sensitivity to Sulfadiazine Silver

Abstract: a $ulfonamlde-realstant organisms have been reported as a Despite several reports of in vitro assays of the antifrequent consequence of the clinical use of sulfaelazine silver, microbial activity of sulfadiazine silver, the specific role of At this bum center, sultfnmide resistance occurred in more sulfadiazine in the antibacterial activity of this salt has not than 80% of gram-negative Isolates. We tested the requirement been defined.' The question of whether sulfadiazine plays a for the Individual antimicrob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

1984
1984
2002
2002

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…AgSD is known to have broad antimicrobial activity and is active against a range of gram‐negative and gram‐positive bacteria and is effective against yeast (24). However, AgSD is also known to be toxic; for example, to bone marrow and fibroblasts (20,24). Thus, the controlled release of AgSD, to limit its cytotoxicity, is believed to be important in the fabrication of AgSD‐medicated wound dressings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…AgSD is known to have broad antimicrobial activity and is active against a range of gram‐negative and gram‐positive bacteria and is effective against yeast (24). However, AgSD is also known to be toxic; for example, to bone marrow and fibroblasts (20,24). Thus, the controlled release of AgSD, to limit its cytotoxicity, is believed to be important in the fabrication of AgSD‐medicated wound dressings.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of the bacterial assay for the skin graft study, two types of bacteria were used: gram‐positive S. aureus and gram‐negative P. aeruginosa . Many authors have performed sensitivity assays for AgSD and have demonstrated that AgSD effectively inhibits the growth of S. aureus and P. aeruginosa (18–20). As shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, it is believed that the AgSD molecule dissociates and that the silver moiety becomes bound to bacterial cells, penetrates the bacterial cell wall, and subsequently is attached toDNA and prevents bacterial proliferation. The sulfadiazine moiety also has a bacteriostatic effect (25). In the present study, a combination of AgSD and laminin modified collagen membrane was shown to facilitate the dermal wound healing process.…”
Section: Discussionmentioning
confidence: 50%
“…However, sulfonamide-resistant organisms have been reported as a frequent consequence of the clinical use of sulfadiazine silver . It was also shown that the sulfadiazine component is not necessary for in vitro sensitivity, and the use of sulfadiazine silver in every case can, therefore, lead to the selection of organisms that are resistant not only to sulfonamides but also to antibiotics of clinical consequence …”
mentioning
confidence: 99%